Hormones, Metabolism and the Benefits of Exercise - Spiegelman, Bruce (Research and Perspectives in Endocrine Interactions,, 2017)
The world is faced with an epidemic of metabolic diseases such as obesity and type 2 diabetes. This is due to changes in dietary habits and the decrease in physical activity. Exercise is usually part of the prescription, the first line of defense, to prevent or treat metabolic disorders. However, we are still learning how and why exercise provides metabolic benefits in human health. This open access volume focuses on the cellular and molecular pathways that link exercise, muscle biology, hormones and metabolism. This will include novel "myokines" that might act as new therapeutic agents in the future.